Vanadium oxysodium fluorophosphate as well as preparation method and application thereof

By heating the reactants in the air, a single reaction is generated by heating the reactants in one step, and introducing conductive materials to form a dual conductive structure, the problems of cumbersome synthesis steps and poor conductivity are solved, and low-cost, high-performance vanadyl oxide fluorine phosphate material is realized, suitable for sodium ion batteries with high energy density and high rate performance.

CN119706782APending Publication Date: 2025-03-28SHANGHAI TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311252214.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode material, the synthesis steps of vanadium phosphate, the equipment dependence is strong, and the conductivity is poor, which limits its application in sodium ion batteries.

Method used

A method of simply heating reactants in the air is used to react in one step to generate high-performance vanadium phosphate sodium, and the conductive material is introduced during and later stages to form an internal and external double conductive structure to improve the conductive properties of the material.

Benefits of technology

It realizes high-performance vanadium phosphate sodium material with low cost and easy to produce on a large scale, significantly improving its conductive performance and cycling stability, and is suitable for sodium ion batteries with high energy density and high rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004470640100000011
    Figure HDA0004470640100000011
  • Figure HDA0004470640100000012
    Figure HDA0004470640100000012
  • Figure HDA0004470640100000013
    Figure HDA0004470640100000013
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion batteries, in particular to sodium vanadium oxyfluorophosphate as well as a preparation method and application thereof. The invention relates to a preparation method of sodium vanadium oxyfluorophosphate, which comprises the following steps: mixing vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride, adding a reagent, grinding, heating, reacting, cooling, washing and drying to obtain the sodium vanadium oxyfluorophosphate. The synthesis cost of the sodium vanadium oxyfluorophosphate is greatly reduced, and large-scale production is facilitated. Meanwhile, the conductivity of the material is greatly improved, so that the dosage of the conductive agent can be reduced, and the proportion of the positive electrode material in an electrode system is increased. And the construction of the sodium ion battery with high energy density and high rate performance is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to sodium vanadium oxyfluorophosphate and a preparation method and application thereof. Background Art

[0002] The development of electric vehicles and large-scale energy storage relies on high-performance lithium-ion batteries. However, the limited content and uneven distribution of lithium resources have caused the manufacturing cost of lithium-ion batteries to rise rapidly. As the most promising alternative to lithium-ion batteries, sodium-ion batteries have the advantages of abundant raw materials and low cost, but their energy density is lower than that of lithium-ion batteries. The development of high-voltage, high-capacity stable sodium-ion cathodes is a key link in realizing the industrialization of sodium-ion batteries.

[0003] At present, mature sodium ion positive electrodes include three types: Prussian blue analogues, layered transition metal oxides and polyanion types. Among them, sodium vanadium oxyfluorophosphate in the polyanion positive electrode has high voltage, good fast charging performance and ultra-stable cycle performance, and has broad application development prospects. Efficient and simple large-scale preparation of sodium vanadium oxyfluorophosphate positive electrode materials with superior performance is the key to promoting the industrial development of sodium ion batteries. At present, the synthesis methods of sodium vanadium oxyfluorophosphate include hydrothermal synthesis, precipitation method and solid phase ball milling synthesis. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the first aspect of the present invention provides a method for preparing sodium vanadium oxyfluorophosphate, which comprises mixing vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride, adding a first solvent for grinding, heating and reacting, cooling, washing and drying to obtain the sodium vanadium oxyfluorophosphate.

[0005] Preferably, the molar ratio of vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride in A1) is 2:(2-2.5):(1-1.2); for example, it can be 2:(2-2.1):(1-1.2), 2:(2-2.2):(1-1.2), 2:(2-2.3):(1-1.2), 2:(2-2.4):(1-1.2), 2:(2-2.5):(1-1.1), etc.

[0006] Preferably, A2) the first solvent is selected from one or more of deionized water and ethanol; ethanol and water can be mixed in any ratio of 1:3, 1:1 or 3:1. The present invention selects water and ethanol with low cost and no pollution, and can play the role of uniformly mixing raw materials.

[0007] Preferably, A3) the volume ratio of the total mole of the vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride to the reagent is 1 mol: (8-10) ml; for example, it can be 1 mol: 8 ml, 1 mol: 9 ml, 1 mol: 10 ml, etc.

[0008] Preferably, the grinding device described in A4) is a mortar.

[0009] Preferably, the heating rate of A5) is 2-5°C / min; the heating rate will affect the crystallinity of sodium vanadium oxyfluorophosphate; if the heating rate is too low, the crystallinity of sodium vanadium oxyfluorophosphate is poor, and if the heating rate is too high, the uniformity of the grain growth of sodium vanadium oxyfluorophosphate is difficult to control. At the heating rate specified in the present invention, both the good crystallinity of sodium vanadium oxyfluorophosphate and the uniform grain growth of sodium vanadium oxyfluorophosphate can be ensured, for example, it can be 2-3°C / min, 3-4°C / min, or 4-5°C / min.

[0010] Preferably, the reaction temperature of A6) is 320-400°C. In the present invention, if the reaction temperature is too low, the reaction cannot occur; if the reaction temperature is too high, the product will decompose and an impurity phase will be generated. For example, the reaction temperature may be 320-340°C, 340-360°C, 360-380°C, 380-400°C, etc.

[0011] Preferably, the reaction time of A7) is 5 to 7 hours; in the present invention, if the reaction time is too short, the sodium vanadium oxyfluorophosphate crystals cannot be completely grown; too long a reaction time will increase the manufacturing cost. Therefore, limiting the reaction time to this time can not only ensure that the sodium vanadium oxyfluorophosphate crystals are completely grown, but also protect the lower manufacturing cost, for example, it can be 5 to 6 hours, 6 to 7 hours.

[0012] Preferably, the atmosphere of the reaction in A8) is one or more of air, nitrogen and argon; preferably, the reaction atmosphere is air, and the product obtained in air has the best performance and the lowest cost.

[0013] Preferably, after cooling in A9), washing and drying are further included.

[0014] Preferably, in A91) feature A9), the cooling to room temperature is about 25°C;

[0015] Preferably, A92) in feature A9), the washing agent is selected from one or more of deionized water and ethanol;

[0016] Preferably, in A93) feature A9), the washing further comprises centrifugation. Preferably, the mixing further comprises a first conductive agent, the first conductive agent being selected from one or more of Super P conductive carbon black, Ketjen black and multi-walled carbon nanotubes. The first conductive agent is used to improve the conductivity of the material, so that the sodium vanadium oxyfluorophosphate has excellent conductivity.

[0017] Preferably, the mass ratio of the first conductive agent to the sodium vanadium oxyfluorophosphate is 0.01 to 0.1: 1. In the present invention, too low a first conductive agent cannot significantly improve the conductivity of the material; too high a first conductive agent will reduce the actual capacity of the material.

[0018] The second aspect of the present invention provides sodium vanadium oxyfluorophosphate, which is prepared by the above-mentioned preparation method of sodium vanadium oxyfluorophosphate.

[0019] A third aspect of the present invention provides a method for preparing a sodium vanadium oxyfluorophosphate composite material, comprising mixing the sodium vanadium oxyfluorophosphate described in claim 6 with a second conductive agent, a binder and a second solvent to obtain the sodium vanadium oxyfluorophosphate composite material.

[0020] Preferably, C1) the second conductive agent is selected from one or more of Super P conductive carbon black, Ketjen black and multi-walled carbon nanotubes;

[0021] Preferably, C2) the binder is selected from carboxymethyl cellulose;

[0022] Preferably, C3) the second solvent is selected from water;

[0023] Preferably, the mass ratio of the sodium vanadium oxyfluorophosphate to the composite material of C4) is 0.8-0.95;

[0024] Preferably, C5) the ratio of the Super P conductive carbon black to the total mass is 0.01-0.1;

[0025] Preferably, C6) the mass ratio of the composite material of Ketjen black and the sodium vanadium oxyfluorophosphate is 0.01-0.1;

[0026] Preferably, C7) the mass ratio of the composite material of the multi-walled carbon nanotubes to the sodium vanadium oxyfluorophosphate is 0.01-0.1;

[0027] Preferably, C8) the mass ratio of the binder to the composite material of sodium vanadium oxyfluorophosphate is 0.02-0.1;

[0028] Preferably, C9) the mass ratio of the second solvent to the second conductive agent is (1:1)-(3:1).

[0029] Super P Conductive Carbon Black is a conductive carbon black prepared by furnace method (MMM method). It is agglomerated from primary particles (primary structure) with a diameter of about 40nm into primary aggregates (secondary structure) of 150-200nm, and then processed by soft agglomeration and artificial compression. The overall shape is grape chain. Its role in lithium-ion batteries is more to disperse primary aggregates of 150-200nm around active substances to form a multi-branched conductive network, thereby reducing the physical internal resistance of the battery and improving electronic conductivity.

[0030] The present invention adopts for the first time a synthesis method of high-performance sodium vanadium oxyfluorophosphate by simply heating the reactants in air, which has the advantages of low cost and easy large-scale production. At the same time, by introducing conductive materials twice during and after the synthesis process, an internal and external double conductive structure is formed, which further improves the various properties of sodium vanadium oxyfluorophosphate and has important application value in the field of sodium ion battery positive electrodes.

[0031] A fourth aspect of the present invention provides a sodium vanadium oxyfluorophosphate composite material, which is prepared by the above method for preparing the sodium vanadium oxyfluorophosphate composite material.

[0032] A fifth aspect of the present invention provides the use of the above-mentioned sodium vanadium oxyfluorophosphate or the above-mentioned sodium vanadium oxyfluorophosphate composite material in a sodium ion battery.

[0033] The present invention has the following technical effects:

[0034] 1) The present invention realizes a simple and low-cost synthesis method for generating high-performance sodium vanadium oxyfluorophosphate by one-step reaction of heating in air, which solves the technical problems of complicated synthesis steps and strong equipment dependence of sodium vanadium oxyfluorophosphate.

[0035] 2) The present invention can synthesize a sodium vanadium oxyfluorophosphate composite material with an internal carbon conductive network by adding a conductive agent (such as carbon nanotubes, Ketjen black and other conductive materials) to the raw materials. The technical problem of poor conductivity of sodium vanadium oxyfluorophosphate is solved. Under the condition of adding a small amount of additional conductive agent, an electrode with high specific capacity can be obtained.

[0036] 3) In the present invention, the synthesized sodium vanadium oxyfluorophosphate or sodium vanadium oxyfluorophosphate with an internal conductive carbon network is ground and mixed evenly with a small amount of Ketjen black to form a conductive network outside the sodium vanadium oxyfluorophosphate, which can further improve the specific capacity of the electrode, especially the capacity under high rate charge and discharge conditions.

[0037] 4) The present invention greatly reduces the synthesis cost of sodium vanadium fluorophosphate and is easy to mass produce. At the same time, it greatly improves the conductivity of the material, thereby reducing the amount of conductive agent used and increasing the proportion of positive electrode materials in the electrode system.

[0038] 5) The improvement of the conductivity in the present invention enables the fast charging performance of the battery to be charged to 70% of the capacity in 3 minutes.

[0039] 6) The cycle stability of the sodium vanadium oxyfluorophosphate composite material in the present invention is improved, and 70% of the capacity is maintained after 2000 cycles, which is beneficial to the construction of sodium ion batteries with high energy density and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Shown is an electron microscope image of sodium vanadium oxyfluorophosphate (NVOPF) synthesized in Example 1 of the present invention.

[0041] Figure 2 Shown is an electron microscope image of the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF) in Example 2 of the present invention.

[0042] Figure 3 Shown is an electron microscope image of the MCNT composite sodium vanadium oxyfluorophosphate (MCNT / NVOPF) positive electrode material in Example 3 of the present invention.

[0043] Figure 4 It is a schematic diagram showing the results of XRD analysis of sodium vanadium oxyfluorophosphate (NVOPF), sodium vanadium oxyfluorophosphate composited with Ketjen black (KB / NVOPF) and sodium vanadium oxyfluorophosphate composite material (MCNT / NVOPF) in Examples 1-3 in Example 4.

[0044] Figure 5 It shows the rate performance of sodium vanadium oxyfluorophosphate (NVOPF) and Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) in Example 5 of the present invention.

[0045] Figure 6 It shows the rate performance of sodium vanadium oxyfluorophosphate (NVOPF) and Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) in Example 6 of the present invention.

[0046] Figure 7 It shows the rate performance of sodium vanadium oxyfluorophosphate (NVOPF-KB) composited with Ketjen black in Example 7 of the present invention.

[0047] Figure 8 It shows the rate performance of sodium vanadium oxyfluorophosphate composited with Ketjen black (KB / NVOPF-0.02-KB) in Example 8 of the present invention.

[0048] Fig. 9 It shows the rate performance of KB / NVOPF-0.05-KB in Example 9 of the present invention.

[0049] Fig.10It shows the rate performance of KB / NVOPF-0.05-KB in Example 10 of the present invention.

[0050] Fig.11 It shows the cycling performance of KB / NVOPF-0.02-KB at 5C rate in Example 11 of the present invention.

[0051] Fig.12 It shows the cycling performance of KB / NVOPF-0.02-KB at 10C rate in Example 11 of the present invention. DETAILED DESCRIPTION

[0052] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0053] See also Figure 1-12 . It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings in this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change in the proportional relationship, or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.

[0054] Example 1

[0055] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate and 10mmol of sodium fluoride were added to 2ml of H 2 O reagent, grind, heat to 360°C at a rate of 5°C / min, react for 6 hours, cool to room temperature 25°C, wash with water and ethanol, centrifuge, and dry to obtain the sodium vanadium fluorophosphate. Figure 1 As shown, electron microscopic observation shows that the synthesized sodium vanadium oxyfluorophosphate (NVOPF) is composed of small particles of about 100 nm aggregated to form large particles of micron size.

[0056] Example 2

[0057] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 40mg of Ketjen black were added to 2ml of H 2O reagent, grind, heat to 360°C at a rate of 5°C / min, react for 6h, cool to room temperature, wash with water and ethanol, and dry to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF) positive electrode material. Figure 2 As shown in the figure, electron microscopic observation shows that in the synthesized Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF) positive electrode material, NVOPF is aggregated from small particles of about 100nm to form large particles of micrometer size, and the conductive agent Ketjen black is evenly distributed in the material. The uniformity of small particles is improved, and the large particles formed by aggregation are more dispersed. This is the result of the growth of NVOPF along the carbon skeleton of Ketjen black.

[0058] Example 3

[0059] 20 mmol of vanadyl sulfate, 20 mmol of sodium dihydrogen phosphate, 10 mmol of sodium fluoride and 40 mg of multi-walled carbon nanotubes (MCNT) were added to 2 ml of H 2 O reagent, grind, heat to 360°C at a rate of 5°C / min, react for 6h, cool to room temperature, wash with water and ethanol, and dry to obtain the MCNT composite sodium vanadium oxyfluorophosphate (MCNT / NVOPF) positive electrode material. Figure 3 As shown, electron microscopic observation shows that the synthesized sodium vanadium oxyfluorophosphate (NVOPF) is aggregated from small particles of about 100 nanometers to form large particles of micron size. Inside the particles, filamentous MCNT can be observed to penetrate the interior of the NVOPF to form micron-sized large particles.

[0060] Example 4

[0061] XRD analysis was performed on the sodium vanadium oxyfluorophosphate (NVOPF), the sodium vanadium oxyfluorophosphate composited with Ketjen black (KB / NVOPF), and the sodium vanadium oxyfluorophosphate composite material (MCNT / NVOPF) in Examples 1-3. Figure 4 As shown, the synthesized sodium vanadium oxyfluorophosphate (NVOPF) has good crystallinity, and its diffraction peak position is basically consistent with that of sodium vanadium oxyfluorophosphate (NVOPF) synthesized by other methods reported in the literature, indicating that this method can successfully synthesize sodium vanadium oxyfluorophosphate (NVOPF). The diffraction data of the synthesized sodium vanadium oxyfluorophosphate (KB / NVOPF) and the sodium vanadium oxyfluorophosphate composite material (MCNT / NVOPF) are basically consistent with those of pure sodium vanadium oxyfluorophosphate (NVOPF), indicating that the addition of the conductive agent will not affect the crystal structure of the synthesized sodium vanadium oxyfluorophosphate (NVOPF).

[0062] Example 5

[0063] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate and 10mmol of sodium fluoride were added to 2ml of H 2The mixture is ground with an O reagent, heated to 320° C. at a rate of 2° C. / min, reacted for 2 hours, cooled to room temperature, washed with water and ethanol, and dried to obtain the sodium vanadium oxyfluorophosphate (NVOPF).

[0064] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 100mg of Ketjen black were added to 2ml of H 2 O reagent is ground, heated to 320° C. at a rate of 2° C. / min, reacted for 2 hours, cooled to room temperature, washed with water and ethanol, and dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) positive electrode material.

[0065] 850 mg of sodium vanadium oxyfluorophosphate (NVOPF) and Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) were added to 3 ml H 2 O, stirred evenly and coated on aluminum foil, heated and dried, and cut into electrode sheets for electrochemical performance testing. The test conditions were: homemade sodium foil as the negative electrode, glass fiber as the separator, and a concentration of 1 mol L -1 NaClO 4 A solution of propylene carbonate (PC) and ethylene carbonate (EC) in a volume ratio of 1:1 was used as the electrolyte. Charge and discharge tests were performed in the range of 2.5V-4.3V.

[0066] like Figure 5 As shown in Figure 2, the capacity of sodium vanadium oxyfluorophosphate (NVOPF) at 0.2C reaches 105 mAh g -1 However, when the charge and discharge rate increases to 0.5C, the capacity drops to 58mAh g -1 , and there is basically no capacity at 1C. This shows that the sodium vanadium oxyfluorophosphate (NVOPF) synthesized by this method can be used as a sodium ion positive electrode material, but its performance is restricted by the problem of poor conductivity. After adding Ketchen black (KB) in the synthesis stage, taking KB / NVOPF-0.1 with a KB addition of 10% as an example, the rate performance of the electrode has been significantly improved, and under the charge and discharge conditions of 5C, it still maintains 85mAh g -1 capacity.

[0067] Example 6

[0068] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate and 10mmol of sodium fluoride were added to 2ml of H 2O is ground, heated to 360° C. at a speed of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the sodium vanadium oxyfluorophosphate (NVOPF).

[0069] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 100mg of Ketjen black were added to 2ml of H 2 O reagent is ground, heated to 360° C. at a rate of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF) positive electrode material.

[0070] 850 mg of sodium vanadium oxyfluorophosphate (NVOPF) and Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) were added to 3 ml H 2 O, stirred evenly and coated on aluminum foil, heated and dried, and cut into electrode sheets for electrochemical performance testing. The test conditions are the same as those in Example 5. Figure 6 As shown in Figure 2, the capacity of sodium vanadium oxyfluorophosphate (NVOPF) at 0.2C reaches 107 mAh g -1 The capacity is 104 mAh g at 0.5C, 1C, 2C, 5C, 10C and 15C respectively. -1 , 99mAh g -1 , 90mAh g -1 , 74mAh g -1 , 59mAh g -1 and 46mAh g -1 This indicates that the sodium vanadium oxyfluorophosphate (NVOPF) electrode prepared under this condition has the ability of high-rate charge and discharge. Due to the improvement of conductivity, KB / NVOPF-0.1 shows higher specific capacity and better rate performance. The capacity reaches 115mAh g-1 under the charge and discharge conditions of 0.2C, and the capacity is 112mAh g-1 under the charge and discharge conditions of 0.5C, 1C, 2C, 5C, 10C and 15C respectively. -1 , 108mAh g -1 , 102mAh g -1 , 90mAh g -1 , 77mAh g -1 and 66mAh g -1 .

[0071] Example 7

[0072] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate and 10mmol of sodium fluoride were added to 2ml of H 2 O is ground, heated to 360° C. at a speed of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the sodium vanadium oxyfluorophosphate (NVOPF).

[0073] The above-obtained 3g sodium vanadium oxyfluorophosphate (NVOPF) was ground and mixed with 30mg Ketjen black (KB) to obtain NVOPF-KB electrode. It was found that the active material was NVOPF and KB with a mass fraction of 1% after being mixed and ground evenly, forming a good conductive network outside the NVOPF.

[0074] 850 mg of the obtained sodium vanadium oxyfluorophosphate (NVOPF-KB) composited with Ketjen black was added into 3 ml H 2 O, stirred evenly and coated on aluminum foil, heated and dried, and cut into electrode sheets for electrochemical performance testing. The test conditions are the same as those in Example 5. Figure 7 As shown in Figure 2, the capacity of the NVOPF-KB electrode reached 120 mAh g at 0.2C charge and discharge. -1 The capacity is 117 mAh g at 0.5C, 1C, 2C, 5C, 10C, 15C and 20C respectively. -1 , 114mAh g -1 , 108mAh g -1 、96mAhg -1 , 82mAh g -1 , 72mAh g -1 and 60mAh g -1 .

[0075] Example 8

[0076] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 40mg of Ketjen black were added to 2ml of H 2 O was ground, heated to 360°C at a rate of 5°C / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.02) positive electrode material. 3g of the obtained KB / NVOPF-0.02 was ground and mixed with 30mg of KB to obtain KB / NVOPF-0.02-KB.

[0077] 850 mg of the obtained Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.02-KB) was added to 3 ml of H 2 O, stirred evenly and then coated on aluminum foil, heated and dried, and then cut into electrode sheets for electrochemical performance testing.

[0078] The two materials were tested using the test method of the above embodiment, such as Figure 8 As shown in Figure 2, the capacity of the KB / NVOPF0.02-KB electrode reached 110 mAh g at 0.2C charge and discharge. -1 The capacity is 108 mAh g at 0.5C, 1C, 2C, 5C, 10C, 15C and 20C respectively. -1 , 105mAh g -1 , 101mAh g -1 , 93mAh g -1 , 84mAh g -1 , 76mAh g -1 and 68mAhg -1 .

[0079] Example 9

[0080] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 100mg of Ketjen black were added to 2ml of H 2 O is ground, heated to 360° C. at a rate of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.05) positive electrode material.

[0081] 3 g of the above-obtained Ketjen black-complexed sodium vanadium oxyfluorophosphate (KB / NVOPF-0.05) and 30 mg of Ketjen black (KB) were ground and uniformly mixed to obtain a KB / NVOPF-0.05-KB electrode.

[0082] like Fig. 9 As shown in Figure 2, the capacity of the KB / NVOPF-0.05-KB electrode reached 112 mAh g at 0.2C charge and discharge. -1 The capacity is 111 mAh g at 0.5C, 1C, 2C, 5C, 10C, 15C and 20C respectively. -1 , 111mAh g -1 , 110mAh g -1 , 106mAh g -1 , 101mAh g -1, 93mAh g -1 and 81mAh g -1 .

[0083] Example 10

[0084] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 200mg of Ketjen black were added to 2ml of H 2 O is ground, heated to 360° C. at a rate of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) positive electrode material.

[0085] 3 g of the above-obtained Ketjen black-complexed sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1) and 30 mg of Ketjen black (KB) were ground and mixed evenly to obtain a KB / NVOPF-0.1-KB electrode.

[0086] The obtained 850 mg of Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.1-KB) was added into 3 ml of H2O with 50 mg of conductive agent Super P, 50 mg of multi-walled carbon nanotubes (MCNT) and 50 mg of binder sodium carboxymethyl cellulose (CMC), stirred evenly and coated on aluminum foil. After heating and drying, it was cut into electrode sheets for electrochemical performance testing.

[0087] like Fig.10 As shown in Figure 2, the capacity of the KB / NVOPF-0.1-KB electrode reached 117 mAh g at 0.2C charge and discharge. -1 The capacity is 113 mAh g at 0.5C, 1C, 2C, 5C, 10C, 15C and 20C respectively. -1 , 110mAh g -1 , 106mAh g -1 , 99mAh g -1 , 92mAh g -1 , 86mAh g -1 and 80mAh g -1 .

[0088] Embodiment 11

[0089] 20mmol of vanadyl sulfate, 20mmol of sodium dihydrogen phosphate, 10mmol of sodium fluoride and 40mg of Ketjen black were added to 2ml of H 2 O is ground, heated to 360° C. at a rate of 5° C. / min, reacted for 6 hours, cooled to room temperature, washed with water and ethanol, and then dried to obtain the Ketjen black composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.02) positive electrode material.

[0090] Then, 3 g of the above-mentioned Ketjen black-composite sodium vanadium oxyfluorophosphate (KB / NVOPF-0.02) positive electrode material was ground and uniformly mixed with 30 mg of Ketjen black (KB) to obtain KB / NVOPF-0.02-KB.

[0091] The test method of the above embodiment was used to test the cycling performance of KB / NVOPF-0.02-KB at 5C and 10C rates, as shown in FIG. Fig.11 , 12 As shown, at a charge and discharge rate of 5C, the initial capacity is 92mAh g -1 After 900 cycles, the capacity is 79 mAh g -1 The capacity retention rate is 85.8%. At a charge and discharge rate of 5C, the initial capacity is 81mAh g -1 After 2000 cycles, the capacity is 59 mAh g -1 , the capacity retention rate is 72.8%.

[0092] The above results show that this synthesis method can synthesize sodium vanadium oxyfluorophosphate polyanion positive electrode materials with high capacity performance, high rate performance and good cycle stability in a low-cost and easy-to-scalable manner, effectively solving the problem of poor conductivity of the material. It can be well applied to the next generation of high-energy density, ultra-fast charging performance and high-stability sodium ion batteries, and can be widely used in small electric vehicles, electric vehicles and large-scale energy storage.

[0093] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing sodium vanadium oxyfluorophosphate, characterized in that: The preparation method comprises the steps of mixing vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride, adding a first solvent for grinding, heating and reacting, and cooling to obtain the sodium vanadyl fluorophosphate.

2. The method for preparing sodium vanadium oxyfluorophosphate according to claim 1, characterized in that: Include at least one of the following technical features: A1) the molar ratio of the vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride is 2:(2-2.5):(1-1.2); A2) the first solvent is selected from one or more of water and ethanol; A3) the volume ratio of the total mole of the vanadyl sulfate, sodium dihydrogen phosphate and sodium fluoride to the reagent is 1 mol: (8-10) ml; A4) the grinding device is a mortar; A5) the heating rate is 2-5°C / min; A6) the reaction temperature is 320-400°C; A7) The reaction time is 5 to 7 hours; A8) the reaction atmosphere is one or more of air, nitrogen and argon; A9) After the cooling, washing and drying are also included.

3. The method for preparing sodium vanadium oxyfluorophosphate as claimed in claim 2, characterized in that: Include at least one of the following technical features: A91) In feature A9), the cooling is to room temperature; A92) In feature A9), the washing agent is selected from one or more of deionized water and ethanol; A93) In feature A9), the washing further comprises centrifugation.

4. The method for preparing sodium vanadium oxyfluorophosphate according to any one of claims 1 to 3, characterized in that: The mixing further includes a first conductive agent, which is selected from one or more of Super P conductive carbon black, Ketjen black and multi-walled carbon nanotubes.

5. The method for preparing sodium vanadium oxyfluorophosphate according to claim 4, characterized in that: The mass ratio of the first conductive agent to the sodium vanadium oxyfluorophosphate is 0.01 to 0.1:

1.

6. A sodium vanadium oxyfluorophosphate, characterized in that: The sodium vanadium oxyfluorophosphate is prepared by the preparation method according to any one of claims 1 to 5.

7. A method for preparing a sodium vanadium oxyfluorophosphate composite material, characterized in that: The sodium vanadium oxyfluorophosphate described in claim 6 is mixed with a second conductive agent, a binder and a second solvent to obtain the composite material of the sodium vanadium oxyfluorophosphate.

8. The method for preparing the sodium vanadium oxyfluorophosphate composite material according to claim 7, characterized in that: Include at least one of the following technical features: C1) the second conductive agent is selected from one or more of Super P conductive carbon black, Ketjen black and multi-walled carbon nanotubes; C2) the binder is selected from carboxymethyl cellulose; C3) the second solvent is selected from water; C4) the mass ratio of the sodium vanadium oxyfluorophosphate to the composite material of the sodium vanadium oxyfluorophosphate is 0.8-0.95; C5) the proportion of the Super P conductive carbon black in the total mass is 0.01-0.1; C6) the mass ratio of the composite material of Ketjen black and the sodium vanadium oxyfluorophosphate is 0.01-0.1; C7) the mass ratio of the composite material of the multi-walled carbon nanotubes and the sodium vanadium oxyfluorophosphate is 0.01-0.1; C8) the mass ratio of the binder to the composite material of sodium vanadium oxyfluorophosphate is 0.02-0.1; C9) The mass ratio of the second solvent to the second conductive agent is (1:1)-(3:1).

9. A sodium vanadium oxyfluorophosphate composite material, characterized in that: The composite material is prepared by the method for preparing the sodium vanadium oxyfluorophosphate composite material according to claim 7 or 8.

10. Use of the sodium vanadium oxyfluorophosphate according to claim 6 or the sodium vanadium oxyfluorophosphate composite material according to claim 9 in a sodium ion battery.